2000
DOI: 10.1046/j.1469-8137.2000.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Organic acids produced by mycorrhizal Pinus sylvestris exposed to elevated aluminium and heavy metal concentrations

Abstract: A cultivation method was developed to enable exposure of ectomycorrhizal plants with intact extramatrical mycelium to solutions containing different concentrations of aluminium or heavy metals. Pinus sylvestris seedlings colonized by Suillus variegatus (two isolates), Rhizopogon roseolus or Paxillus involutus (two isolates) were used. Seedlings were transferred to Petri dishes containing glass beads and exposed to elevated concentrations of Al, Cd, Cu, or Ni in two ways : immediately following transfer ; and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(80 citation statements)
references
References 56 publications
5
72
1
2
Order By: Relevance
“…However, R. roseolus did not show specificity for either pine species, as mycorrhizae were found on both species of pines. These findings concur with results of other reports, where R. roseolus colonized roots of both Scots pine and stone pine seedlings (Ahonen-Jonnarth et al 2000;Rincón et al 2001). According to this high potential for mycorrhization, R. roseolus has been recommended for its use in forest nursery mycorrhization programs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, R. roseolus did not show specificity for either pine species, as mycorrhizae were found on both species of pines. These findings concur with results of other reports, where R. roseolus colonized roots of both Scots pine and stone pine seedlings (Ahonen-Jonnarth et al 2000;Rincón et al 2001). According to this high potential for mycorrhization, R. roseolus has been recommended for its use in forest nursery mycorrhization programs.…”
Section: Discussionsupporting
confidence: 91%
“…However, within the genus there are other species of commercial interest, such as R. rubescens (Hall et al 2001) which sells for up to 650 € per kg in Japan (Wang et al 2002). Rhizopogon roseolus has a high potential in forest nursery mycorrhization programs because of its high capacity for colonizing young pine seedling roots (Ahonen-Jonnarth et al 2000;Rincón et al 2001). This ability and its proven antagonistic effect on Fusarium spp.…”
Section: Grown In Containersmentioning
confidence: 99%
“…Furthermore, Al can be detoxified by complexation with low molecular weight organic anions (Ma et al 2001;Ryan et al 2001). Ectomycorrhizal tree seedlings have been found to excrete more oxalate than non-mycorrhizal tree seedlings in response to Al in axenic conditions (Ahonen-Jonnarth et al 2000).toxicity is reported, many of these studies are confined to coniferous plants (Cumming and Weinstein 1990;Hentschel et al 1993;Schier and McQuattie 1996;Ahonen-Jonnarth et al 2003;Scho¨ll et al 2005) and the concentrations of Ca and Mg in ectomycorrhizal tree seedlings are higher, lower or equal compared to non-mycorrhizal seedlings under Al toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Since mycorrhizal fungi exude a range of organic acids (Lapeyrie et al 1987) or produce slime capable of binding metals, it is possible that organic compounds released by mycorrhizal fungi are responsible for the amelioration of metal toxicity in mycorrhizal plants. Stimulation of oxalic acid production by Al and Cu in mycorrhizal and nonmycorrhizal roots has been reported, especially with certain ectomycorrhizal fungi (Jonnarth et al 2000). Jongbloed et al (1992) found that Lactarius rufus Fr.…”
Section: Discussionmentioning
confidence: 99%